Identification of a second linkage group carrying genes controlling resistance to downy mildew (Plasmopara halstedii) in sunflower (Helianthus annuus L.) - Bert, P. F.; Tourvieille de Labrouhe, D.; Philippon, J.; Mouzeyar, S.; Jouan, I.; Nicolas, P.; Vear, F. (Theoretical and applied genetics, 2001)
A sunflower line, XRQ, carrying the gene Pl5, which gives resistance to all French downy mildew races shows cotyledon-limited sporulation in seedling immersion tests; consequently, segregations in crosses with other downy mildew resistance sources were tested both by this method and by a secondary infection on leaves. Pl5 was found to segregate independently of Pl7 (HA338) but to be closely linked, or allelic, with Pl8 (RHA340). F3 and F4 progenies from a cross with a line containing Pl2 showed that Pl5 carries resistance to race 100 which segregates independently of Pl2. The Pl5 gene was mapped on linkage group 6 of the Cartisol RFLP map, linked to two RFLP markers, ten AFLP markers and the restorer gene Rf1. Tests with downy mildew race 330 distinguished Pl5 and Pl8, the first being susceptible, the second resistant, whereas both these genes were active against race 304 to which Pl6 (HA335) and Pl7 gave susceptibility. It is concluded that Pl5 and Pl8 are closely linked on linkage group 6 and form a separate resistance gene group from Pl6/Pl7 on linkage group 1. The origins of these groups of downy mildew resistance genes and their use in breeding are discussed.